2008
DOI: 10.1107/s1744309108001206
|View full text |Cite
|
Sign up to set email alerts
|

Crystallization of the extracellular rubber oxygenase RoxA fromXanthomonassp. strain 35Y

Abstract: Rubber oxygenase A (RoxA) from Xanthomonas sp. strain 35Y is an extracellular dioxygenase that is capable of cleaving the double bonds of poly(cis-1,4-isoprene) into short-chain isoprene units with 12-oxo-4,8-dimethyltrideca-4,8-diene-1-al (ODTD) as the major cleavage product. Crystals of the dihaem c-type cytochrome RoxA were grown by sitting-drop vapour diffusion using polyethylene glycol as a precipitant. RoxA crystallized in space group P2 1 , with unit-cell parameters a = 72.4, b = 97.1, c = 101.1 Å , = 9… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…The four Fe sites were located with SHELXD (41). SHARP (42) was used for site refinement and phase calculations (15). The quality of the resulting electron density map was sufficient for model building using Coot (43), and a nearly complete model was built manually before crystallographic refinement was carried out with REFMAC (44).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The four Fe sites were located with SHELXD (41). SHARP (42) was used for site refinement and phase calculations (15). The quality of the resulting electron density map was sufficient for model building using Coot (43), and a nearly complete model was built manually before crystallographic refinement was carried out with REFMAC (44).…”
Section: Methodsmentioning
confidence: 99%
“…Crystals of RoxA were obtained by the sitting drop vapor diffusion method as described previously (15). A fourwavelength anomalous dispersion experiment was carried out at the K-edge of iron to optimally exploit the phasing power of the two metal ions in the heme groups of RoxA (15).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Determination of the recently solved three-dimensional structure of the RoxA Xsp protein showed that the N-terminal heme has only one axial amino acid ligand (H 195 ) on the proximal side and that dioxygen represents the distal heme ligand (18,19). The N-terminal heme constitutes the active site of RoxA.…”
Section: Identification Cloning and Expression Of Roxa Orthologs Inmentioning
confidence: 99%